Observation of phonons with resonant inelastic x-ray scattering - Yavaş, Hasan; Veenendaal, M. van; Brink, J. van den; Ament, L. J. P.; Alatas, A.; Leu, B. M.; Apostu, M.-O.; Wizent, Nadja; Behr, G.; Sturhahn, W.; Sinn, H.; Alp, E. E. (Journal of physics. Condensed matter, 2010)
Phonons, the quantum mechanical representation of lattice vibrations, and their coupling to the electronic degrees of freedom are important for understanding thermal and electric properties of materials. For the first time, phonons have been measured using resonant inelastic x-ray scattering (RIXS) across the Cu K-edge in cupric oxide (CuO). Analyzing these spectra using an ultra-short core-hole lifetime approximation and exact diagonalization techniques, we can explain the essential inelastic features. The relative spectral intensities are related to the electron-phonon coupling strengths.
Gesehen am 31.05.2024